Anisotropic spin-1/2 XXZ chains with uniform gamma interaction - S. Mahdavifar; D. C. Liu (Scientific Reports)
Abstract In this study, we delve into the intricate ground state phase diagram of anisotropic spin-1/2 XXZ chains under the uniform Gamma interaction. Employing the robust infinite time evolving block decimation (iTEBD) technique and the Lanczos technique, we meticulously obtain the model’s ground state properties. Complementing our numerical analysis, we derive analytical approximations through a mean-field framework, transposed into the fermionic representation. Our investigation rigorously scrutinizes the energy spectrum, distinguishing between gapped and gapless domains at absolute zero. Furthermore, we thoroughly examine various order parameters including magnetization, staggered magnetization, chirality, and spin nematicity, which demarcate the diverse phases within the ground state phase diagram, each characterized by its unique long-range order.